When does proactivity have a cost? Motivation at work moderates the effects of proactive work behavior on employee job strain - Strauss, K.; Parker, Sharon; O'Shea, D. (Academic Press, 2017)
The literature on proactivity has focused primarily on its positive performance outcomes. However, the effects of proactive behavior on employees’ well-being are relatively unknown. We theorize that when an individuals’ motivation at work is characterized by pressure and coercion (high controlled motivation), with no compensatory intrinsic interest in or identification with the work (low autonomous motivation), proactive behavior is likely to deplete employees’ resources, resulting in job strain. We tested this proposition in a lagged study of 127 employee-supervisor dyads across a variety of sectors. As expected, supervisor-rated proactive work behavior was positively associated with job strain when controlled motivation was high and when autonomous motivation was also low. Under all other conditions, there was no effect of proactive behavior on job strain. For example, when individuals experienced high controlled motivation yet also experienced autonomous motivation, there was no effect of proactive behavior on job strain. In sum, proactive behavior has costs in terms of job strain only when employees experience a sense of pressure and obligation in their work in the absence of any compensating autonomous motivation.